Effectiveness Test of Gel Preparations from Ethanol Extract of Gotu Kola Leaves (Centella asiatica L.) for Wound Healing in Mice (Mus musculus) - Islami, Deri; Khasanah, Nida Nurul; Hendrika, Yan (JURNAL PROTEKSI KESEHATAN, 2024)
Pegagan leaves (Centella asiatica L.) are reported to have potential as an anti-oxidant, anti-microbial agent, collagen synthesizing agent, and wound healing agent. Pegagan has components namely triterpenoids and essential oils. Triterpenoids can help wound healing, increase anti-oxidant levels, and increase blood supply to the wound area. The purpose of this study was to determine the difference in the level of wound healing between mice given a gel preparation from ethanol extract of gotu kola leaves, untreated mice and with povidone iodine. Assessment of wound healing was done by macroscopic observation by comparing wound healing between negative control, positive control, 5% formula, 10% for-mula, and 15% formula. The sig value on day 3 was 0.082, day 5 was 0.052, day 7 was 0.240 showing p>0.05 so it can be concluded that there was no significant difference in each group on days 3, 5 and 7. Whereas on day 11 the sig value was 0.011 and day 14 the sig value was 0.006 in the ANOVA test showing p<0.05 so it can be concluded that on days 11 and 14 each group had significant differences.